Heparanase is a predictive marker for high thrombus burden in patients with ST-segment elevation myocardial infarction - (:unkn) unknown (TAYLOR & FRANCIS LTD, 2019)
Objective: Heparanase (HPA) is an endo-beta-D-glucuronidase capable of degrading heparin sulphate (HS) and heparin side chains. HPA plays a role in tumour growth, angiogenesis, cell invasion and in activation of the coagulation system. We aimed to investigate the relationship between HPA and thrombus burden (TB) in patients with ST-Segment Elevation Myocardial Infarction (STEMI). Methods: This prospective study enrolled 187 patients with STEMI who were treated with primary percutaneous coronary intervention (pPCI). Blood samples were taken to determine serum HPA levels prior to coronary angiography and heparin administration. Serum HPA analysis was performed with a commercially available Human Elisa kit. Results: Patients were divided into two groups: high TB (n:58) and low TB (n:129) group. Serum HPA levels were significantly higher in patients with high TB than low TB [250.1 (188.5-338.1) vs. 173.6 (134.3-219.8) pg/mL] (p < 0.001). Serum HPA levels were higher in patients with no-reflow phenomenon compared with others [(409.3 (375.6-512.5) pg/mL vs. 186.2 (144.2-247.4) pg/mL, p < 0.001]. In multiple logistic regression analysis HPA was a predictor of high TB. Conclusion: Elevated HPA level in patients with STEMI is related to high TB. Furthermore, increased HPA level may be associated with thrombotic complications such as no-reflow phenomenon in patients with STEMI.
Keywords: Atherosclerosis; heparanase; myocardial infarction; thrombosis; no-reflow; PERCUTANEOUS CORONARY INTERVENTION; PROCOAGULANT ACTIVITY; INHIBITORS